ONE WEEK ONE ARTICLE PROGRAM IN READING CLASS (A CASE STUDY AT MATHLAUL ANWAR UNIVERSITY) - Yudi Rahmatullah (English Department - University of Sultan Ageng Tirtayasa, 2016)
The research focused on the implementation of one week one article program in improving students’ reading skill and vocabulary mastery. The research was conducted by using qualitative research. The participant of the research was the first semester students of English Department in Mathla’ul Anwar University. There were 53 students taken as the subject. The collecting data Techniques were observation, interview, and questionnaire. The data were analyzed by reduction, display, and conclusion of the data. The result of the research showed that firstly, the implementation of one week one article program is able to improve students’ reading skill and vocabulary mastery. Secondly, the students actively selected, discussed and presented the article in the implementation of one week one article program. Thirdly, the students used reading techniques in the implementation of one week one article program. The last, the students pronounced English words properly in the implementation of one week one article program. It can be concluded that the implementation of one week one article program is able to improve students’ reading skill and vocabulary mastery; in addition the students actively prepared the article and pronounce the vocabulary correctly.